STUDI KELAYAKAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PORTAL UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN PEMAHAMAN KONSEP SISWA - Farda Nihayan Naja; Ahmad Khoiri; Pamungkas Stiya Mulyani (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2022)
The research aims to validation an augmented reality portal learning media to increase learning motivation and students' concept understanding, with ADDIE development models (analysis, design, develop, implement, evaluate). Data gathering techniques by observation, interview, questionnaire, and test. Instruments used in data collection of media validation, motivational questionnaire, and concept comprehension tests. The data analysis techniques used are validation for media analysis and n-gain tests to calculate increased motivation for learning and concept understanding. Research shows that Media fulfill valid criteria with the percentage value of materials at 85%, media expert at 96.875%, eligibility at 93.585%.